2015
DOI: 10.1016/j.jped.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Colonic transit in children and adolescents with chronic constipation

Abstract: Nuclear transit study distinguished two colonic dysmotility patterns and was useful for guiding refractory patients to specific therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The European & North American Societies for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN and NASPGHAN) in their most recent evidence-based recommendations have also stressed the importance of enquiry about stool consistency in the evaluation of constipation in children [ 14 ]. Stool form (consistency) correlates well with gut transit time, which is delayed in children with functional constipation [ 15 16 17 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The European & North American Societies for Pediatric Gastroenterology Hepatology and Nutrition (ESPGHAN and NASPGHAN) in their most recent evidence-based recommendations have also stressed the importance of enquiry about stool consistency in the evaluation of constipation in children [ 14 ]. Stool form (consistency) correlates well with gut transit time, which is delayed in children with functional constipation [ 15 16 17 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Associations of the transit pattern with the type of RFC clinical manifestation have been identified. 13 , 16 Pioneering researchers using this investigation tool have found that patients with a slow colonic transit pattern do not respond to retrograde enemas and may have neurotransmitter deficiencies. 16 Data from the pediatric population are not yet sufficient to define surgical indications based on this type of investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were included in a study for scintigraphic assessment of colonic transit and continued to be systematically followed-up on the same basis. 13 The evaluation was systematized, the attendance to follow-up consultations was monitored, and families were asked about their access to the medication, either with their own resources or through donations. They were also asked about possible side effects of the medication and advised against modifying medication dose without medical consultation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gamma scintigraphy is another technique that has long been used to study colonic transit [42,43], including within paediatric population, [44]. The method uses a γ-emitting radioactive isotope.…”
Section: Gamma Scintigraphymentioning
confidence: 99%